Health Inequality among Chinese Older Adults: The Role of Childhood Circumstances - Binjian Yan; Xi Chen; Thomas M. Gill (Global Labor Organization (GLO), 2020)
This paper examines the extent to which childhood circumstances contribute to health inequality in old age and how the contributions may vary across key dimensions of health. We link the China Health and Retirement Longitudinal Study (CHARLS) in 2013 and 2015 with its Life History Survey in 2014 to quantify health inequality due to childhood circumstances for which they have little control. We evaluate comprehensive dimensions of health ranging from cognitive health, mental health, physical health, self-rated health to mortality. Our analytic sample includes about 8,000 Chinese persons age above 60. Using the Shapley value decomposition approach, we first show that childhood circumstances may explain 1-23 percent of health inequality in old age across multiple health outcomes. Second, while both direct health-related circumstances and indirect health-related circumstances contribute significantly to health inequality, the latter tends to be more sizable. Our findings support the value of a life course approach in identifying the key determinants of health in old age.
Keywords: I14; D63; I18; J13; J14; 330; Life course approach; Inequality of opportunity; Physical health; Cognitive ability; Mental health; Mortality